2021
DOI: 10.3389/fpsyt.2021.792168
|View full text |Cite
|
Sign up to set email alerts
|

Apathy as a Risky Neuropsychiatric Syndrome of Progression From Normal Aging to Mild Cognitive Impairment and Dementia: A Systematic Review and Meta-Analysis

Abstract: Background: Apathy has been suggested as a potential predictor of mild cognitive impairment (MCI) progression to dementia. Whether it might predict the transition from normal cognitive function to cognitive impairment has been less studied. The current study aimed to provide a comprehensive summary of the evidence on the association between apathy and the transition from normal cognitive function to cognitive impairment.Methods: We searched the PubMed, Embase, and Web of Science databases for longitudinal pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…Both apathy and depression consistently predict an increased risk for the development of NCDs. A meta‐analysis of 10 studies that included over 22,000 individuals classified as cognitively normal found that apathy was associated with a 2‐fold increased risk of cognitive impairment 65 . Indeed, it has been suggested that apathy may be a pre‐dementia phenotype 16 .…”
Section: Definitions and Clinical Presentation Of Apathy And Depressionmentioning
confidence: 99%
“…Both apathy and depression consistently predict an increased risk for the development of NCDs. A meta‐analysis of 10 studies that included over 22,000 individuals classified as cognitively normal found that apathy was associated with a 2‐fold increased risk of cognitive impairment 65 . Indeed, it has been suggested that apathy may be a pre‐dementia phenotype 16 .…”
Section: Definitions and Clinical Presentation Of Apathy And Depressionmentioning
confidence: 99%
“…However, no previous work has operationalized apathy using the more conservative MBI classification approach, which offers greater specificity. A previous systematic review and meta‐analysis in NC revealed greater apathy‐associated rates of incident dementia, with a pooled HR of 3.42 from three included studies 21 . Similarly, in MCI, meta‐analysis demonstrated greater apathy‐associated rates of incident dementia, with a pooled HR of 1.54 from 11 included studies 22 .…”
Section: Discussionmentioning
confidence: 92%
“…A previous systematic review and meta‐analysis in NC revealed greater apathy‐associated rates of incident dementia, with a pooled HR of 3.42 from three included studies. 21 Similarly, in MCI, meta‐analysis demonstrated greater apathy‐associated rates of incident dementia, with a pooled HR of 1.54 from 11 included studies. 22 The relatively higher HR in NC versus MCI from these meta‐analyses is consistent with our findings, in which individuals with both NC and MCI were included, allowing for direct comparisons between cognitive groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to physical frailty, apathy may impair cognitive function 10,44 and ADL 10 as well as reduce social support. 45 In the present study, individuals with apathy reported more frequent problems in IADL, oral function, and cognitive function compared to individuals without apathy.…”
Section: Discussionmentioning
confidence: 99%